Non-resident rental housing application / Nurul Afiqah Ayob - Ayob, Nurul Afiqah (2019)
This mobile application is personally developed for UiTM Tapah students, especially non-resident students in finding off-campus rental housing. Students always complained that they are having difficulties in finding rental housing around the Tapah area. Therefore, this mobile application is developed to help students in finding off-campus rental housing around the Tapah area. This project was split into 6 phases: Planning, Analysis, Design, Implementation, Testing and Evaluation and Documentation. The requirements for this project was gathered through an interview with a staff of the Non-Resident Unit and survey among students. This project is developed based on a preliminary survey conducted among 71 students. Usability testing is applied to evaluate the feedback of students regarding their satisfaction in this mobile application. The result from the survey shows 94.4% students are satisfied with the overall system. However, there are still some future work needs to be done to improve this project. The future developer can make enhancement of this current application.